Challenges Affecting Conservation Areas With Unsustainable Harvesting Of The Mopane Worms - Mr Takalani Ernest Dzhanngi; Thizwilondi Madima; Justice Makhanikhe (CV. RADJA PUBLIKA, 2025)
Challenges affecting conservation areas with unsustainable harvesting of the Mopane worms This study explored the challenges affecting conservation areas with unsustainable harvesting of the Mopane worms. It was observed that conservation areas in South Africa continued to use pesticides and deforestation, which could potentially lead to the extinction of Mopane worms. Pesticides were found to damage the leaves of Mopane trees, adversely affecting the mass production of Mopane worms. As Mopane worms are an indigenous staple crucial for local livelihoods, their decline poses significant concerns for the communities dependent on them. The overharvesting of Mopane worms without adequate ecosystem protection led to environmental unsustainability. This study highlighted the need for conservation areas to adopt alternative pest control methods and avoid deforestation to protect Mopane worm breeding habitats. The study was guided by the Afrocentricity Theory developed by Molefi Kete Asante in 2020, which emphasizes recognizing African values and perspectives. A qualitative research design was employed, utilizing purposive and snowball sampling methods for selecting participants. Semi-structured interviews were conducted, and thematic data analysis was used to interpret the findings. Data saturation was achieved with the 13th participant. The study revealed that sustainable management and harvesting practices are essential for preserving Mopane worms for future generations. Implementing integrated pest management strategies and promoting conservation practices that do not compromise Mopane worm habitats are crucial for ensuring the long-term viability of Mopane worm populations. The study concluded that balancing conservation efforts with local economic needs is vital for the sustainable harvesting of Mopane worms. Effective measures must be taken to mitigate environmental impacts while supporting the livelihoods of the local communities.